A predictive study on the role and function of the dental hygienist in Taiwan* - Y-A Cheng (Journal compilation 2007 Blackwell Munksgaard, 2007)
The purpose of this study was to achieve a consensus on the work roles and scope of practice of dental hygienists in Taiwan and to rank the results according to their importance.